Toward Community Coverage on Self-Screening, Diagnosis, and Help-Seeking Behavior for Both Gender Victims of Intimate Partner Violence (IPV) in a Kenyan Setting: The Development of IPV–Brief Self-Screener (IPV-BSS) Version of the WHO-IPV Instrument. Issue 17 (September 2021) - Mutiso, Victoria N.; Musyimi, Christine W.; Gitonga, Isaiah; Rebello, Tahilia J.; Tele, Albert; Pike, Kathleen M.; Ndetei, David M.
Intimate partner violence (IPV) is a major public health concern. The prevalence of IPV in women in Kenya is in the range of 41% to 45% but has also been reported in 20% of men. The most widely used instrument for the screening and diagnosis of IPV is the World Health Organization–Intimate Partner Violence (WHO-IPV). However, it is lengthy for routine large-scale screening and is administered by a trained person, thus limiting the number it can reach for screening. There is therefore a need for a shorter screening version that can be self-administered to reach critical masses. Those who screen positive can then be subjected to the longer version. In addition, the short version should be culturally sensitive, can be used by either gender, can be used in busy clinical settings as the patients wait to be attended to, and can be used for large-scale community populations to raise awareness and promote help-seeking behavior. It should be applicable in similar cultural settings and is aligned to the longer version of the WHO-IPV instrument. This study aimed to develop such a tool. We administered the WHO-IPV to two groups: firstly, postnatal mothers attending postnatal clinics and secondly, men and women attending general clinics to which they had been referred. These referrals were by traditional healers (TH), faith healers (FH), and community health workers (CHW) who had been trained to screen for mental disorders using the Mental Health Gap Action Programme–Intervention Guide (mhGAP-IG) master checklist. Using factor analysis of the scores, we came up with questions that had the highest predictive value for different types of IPV diagnosis and which could therefore be used for self-screening purposes. We call the tool the Intimate Partner Violence–Brief Self-Screener (IPV-BSS; Adapted by the Africa Mental Health Research and Training Foundation from the WHO-IPV).